2020
DOI: 10.1155/2020/3680397
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Lipid Intake and Chronic Kidney Disease

Abstract: The incidence of chronic kidney disease (CKD) is associated with major abnormalities in circulating lipoproteins and renal lipid metabolism. This article elaborates on the mechanisms of CKD and lipid uptake abnormalities. The viewpoint we supported is that lipid abnormalities directly cause CKD, resulting in forming a vicious cycle. On the theoretical and experiment fronts, this inference has been verified by elaborately elucidating the role of lipid intake and accumulation as well as their influences on CKD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 131 publications
(181 reference statements)
0
12
0
3
Order By: Relevance
“…Hyperlipidemia is commonly related to a high intake of diets rich in fatty acids and obesity ( 45 , 46 ). It is described that the abnormal deposition of fat in adipose tissue and in other organs, such as the liver and kidneys, can be considered an important risk in the follow-up of pathologies, including CKD ( 45 , 47 , 48 ). The presence of dyslipidemia is reported in all stages of CKD, with impairment of the glomerular filtration barrier, tubular damage, and proteinuria ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperlipidemia is commonly related to a high intake of diets rich in fatty acids and obesity ( 45 , 46 ). It is described that the abnormal deposition of fat in adipose tissue and in other organs, such as the liver and kidneys, can be considered an important risk in the follow-up of pathologies, including CKD ( 45 , 47 , 48 ). The presence of dyslipidemia is reported in all stages of CKD, with impairment of the glomerular filtration barrier, tubular damage, and proteinuria ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is described that the abnormal deposition of fat in adipose tissue and in other organs, such as the liver and kidneys, can be considered an important risk in the follow-up of pathologies, including CKD ( 45 , 47 , 48 ). The presence of dyslipidemia is reported in all stages of CKD, with impairment of the glomerular filtration barrier, tubular damage, and proteinuria ( 47 ). Our HFD and HFDV rats showed higher plasma levels of cholesterol and triglycerides than SD and VDD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is a common symptom in DM. Continuous renal filtration of lipids in rats with DM leads to chronic kidney injury, albuminuria, and glomerulosclerosis [ 45 ]. In agreement with our findings, a study reported that treatment with L-lysine significantly alleviated diabetic dyslipidemia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on protein sources suggest that fish proteins do not affect albuminuria as much as proteins from meat and meat products [ 28 , 46 ], and the same could be true for fat. Several studies on omega-3 polyunsaturated FA supplementation report beneficial effects on urinary albumin excretion and kidney function in patients with and without diabetes [ 47 , 48 , 49 , 50 ], possibly by decreasing inflammation and endothelial dysfunction, as well as reducing hypertension and dyslipidemia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%